2016
DOI: 10.1140/epjc/s10052-016-4322-3
|View full text |Cite
|
Sign up to set email alerts
|

Inflation as de Sitter instability

Abstract: We consider cosmological inflation generated by a scalar field slowly rolling off from a de Sitter maximum of its potential. The models belong to the class of hilltop models and represent the most general model of this kind in which the scalar potential can be written as the sum of two exponentials. The minimally coupled Einsteinscalar gravity theory obtained in this way is the cosmological version of a two-scale generalization of known holographic models, allowing for solitonic solutions interpolating between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In this context, the existence of exact solutions might be helpful for calculations. These topics are currently under study [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the existence of exact solutions might be helpful for calculations. These topics are currently under study [15].…”
Section: Resultsmentioning
confidence: 99%
“…It is then a promising candidate to describe the evolution of an inflationary universe. 1 In the following sections we shall investigate the main mathematical aspects of the solutions derived from the potential (1.4), reserving a study of their implications for observational cosmology to future work [15]. The main result of our investigation is that the solutions admitting exponential inflation, like (1.5), correspond to specific boundary conditions where the scalar field is initially at rest on the maximum of the potential, while generic initial conditions give rise to power-law inflation for a range of values of the parameter β.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also found seven candidate genes that have shown a significant association with ADHD using the genome scan and candidate gene approach: DRD4, DRD5, DAT, DBH, 5-HTT, HTR1B and SNAP-25 (161). In addition, researchers have also suggested that neurological abnormalities may contribute to the etiology of ADHD, probably precipitated and exacerbated by both nature and nurture (162). Children diagnosed with ADHD have been shown to have decreased volume of the prefrontal cortex and parietal cortex.…”
Section: Psychosis and Vitamin D Clinical Studiesmentioning
confidence: 99%
“…As it can be easily checked, the potential (3) is invariant under the transformation β → 1 β , and similar potentials were studied in Refs. [27][28][29]. Actually, potentials with the symmetry β → 1 β are related to holographic models, see Refs.…”
Section: Essential Features Of Inverse Symmetric Attractors and Smentioning
confidence: 99%
“…Actually, potentials with the symmetry β → 1 β are related to holographic models, see Refs. [27][28][29] and references therein. Let us now discuss the interesting features of the model (3), and firstly we discuss two limiting cases of the parameter β, namely the cases β > 1 and β < 1.…”
Section: Essential Features Of Inverse Symmetric Attractors and Smentioning
confidence: 99%